AN EXPLORATORY STUDY OF SHOPRITE AND CHECKERS AS A MEANINGFUL BRAND IN THE CONTEXT OF FOOD WASTE MANAGEMENT - Ralane, Langelihle (The IIE, 2022)
Background: Food waste and loss continue to be a problem globally. This is despite many people going hungry in the world, especially in sub-Saharan Africa. A lot of food is wasted during the early stages of production in lowmiddle income countries such as South Africa. But recent wastages in postharvest to consumer supply chain stages put retailers such as Shoprite and Checkers at the centre of food waste management research. Objective: Thus, the main objective of this study was to describe how Shoprite and Checkers managed or failed to manage the sourcing and processing of raw materials to minimize food loss and food waste. Method: To achieve this objective, this study applied a secondary qualitative research as a design. Content analysis of text data in the form of existing online media materials on the subject of Shoprite and Checkers and food waste was applied. Three online articles were sourced and analysed using a thematic analysis technique as a method of data analysis. Findings: From this analysis it was found that food waste and loss happen at the agricultural or production levels in Shoprite and Checkers’ supply chain. This was despite efforts made by the group to reduce food waste, and despite the fact that the retailer does not directly control the independent large-scale farmers responsible for food production. It was also found that food waste leads to waste of embedded resources such as water, land, capital and labour. At the same time, it was found Shoprite and Checkers makes efficient effort towards preventing and reducing food waste/loss. It does this by using predictive analytical tools such as artificial intelligence and machine learning to mitigate against food waste (South African Good News, 2022). The retailer also demonstrated to be socially and environmentally conscious, thus fulfilling its endeavours towards being a brand with purpose.
Keywords: Hunger; Healthy brands; Retail; Agriculture